Optical and Thermal Characterization of Zinc Oxide-Based Ceramic Using Pyroelectric and Photopyroelectric Techniques - Mohd Shapee, Sabrina (2009)
The advantage of wide electrical band-gap of zinc oxide (ZnO) semiconductor has been used in many applications particularly as varistors, which are ceramic devices with highly non-linear current-voltage characteristics. For ZnO-based varistor system, one or more additive oxides such as antimony oxide (Sb2O3), bismuth oxide (Bi2O3) and cobalt oxide (Co3O4) are the main tools that improve the nonlinear response and the stability of ZnO varistor. The thermal and optical characteristics of ZnO-based ceramic have been carried out at room temperature using pyroelectric and photopyroelectric techniques, respectively, that use polyvinylidene fluoride film as detector. In thermally thick regime, the thermal diffusivity value is obtained from the plot of the product of modulation frequency (f) times pyroelectric amplitude signal versus f. The thermal diffusivity obtained for pure ZnO ceramic sample without potassium bromide (KBr) (0.079 cm2s-1) close to literature values, indicates the reliability of the present set up. The thermal diffusivity of doped ZnO ceramic in KBr matrix was prepared by mixing the ground ceramic with KBr and pressed into a pellet form. Before the sample was attached to the pyroelectric detector it was covered with carbon soot to turn it into an optically opaque condition. It is observed that the thermal diffusivity of ceramic ZnO doped with Bi2O3 in the KBr matrix increases with the increase of Bi2O3 mol percentage. The photopyroelectric spectrometer has been used to obtain optical absorption spectrum of ZnO based ceramic doped with various mol percentages of Bi2O3, Co3O4 and Sb2O3. The photopyroelectric optical spectra of thin layer of ceramic samples, put directly on photopyroelectric detector, were used to determine the band-gap energy of the samples. The results indicate that for all dopants the band-gap energy of ZnO decreases with the increase of dopant mol percentage. Microstructural characterization has been made on the ZnO-based ceramic by addition of different metal oxides. All of the samples were characterized using scanning electron microscopy (SEM) and X-ray diffraction (XRD).